Are Children Suffering From Congenital Pseudarthrosis of the Tibia Associated With Decreased Bone Strength? - Yang, Ge; Xu, Siyu; Mei, Haibo; Zhu, Guanghui; Liu, Yaoxi; Tan, Qian; Yu, Hui (Frontiers in Pediatrics, 2022)
Background: Congenital pseudarthrosis of the tibia (CPT) is a rare and difficult-to-treat congenital disease in neonates. Our previous study found that exosomes derived from serum of children with CPT inhibit bone formation. In this study, we used ultrasound bone densitometry to detect the bone strength differences between hospitalized children with CPT and with non-metabolic diseases to determine the bone strength of children with CPT. Methods A total of 37 children with CPT with a mean age of 3.14 ± 1.81 years and 40 hospitalized children with a mean age of 3.32 ± 2.66 years with supracondylar fracture of the humerus and without a bone metabolic disease (control group) were recruited in our hospital. The ultrasonic bone densitometer was used to examine the bilateral calcaneus of the subjects. We collected the broadband ultrasonic attenuation (BUA), speed of sound (SOS), quantitative ultrasound index (QUI), bone strength index (STI) and bone mineral density estimation (BMDe) values. Multivariable regression was used to examine the associations between quantitative ultrasound measurement differences and age, body mass index (BMI), neurofibromatosis type 1 (NF1) and CPT Crawford type. Intra-class correlation coefficient (ICC) was calculated to estimate intra- and inter-rater agreements. Results 74 calcaneus scans were taken from CPT patients (23 boys and 14 girls) and 80 calcaneus scans were taken from the control (24 boys and 16 girls). The CPT patients exhibited significantly lower SOS (1,368.75 ± 136.78 m/s), STI (7.2319 ± 38.6525), QUI (8.2532 ± 56.1720), and BMDe (−0.0241 ± 0.3552 g/cm3) than the control (SOS: 1,416.02 ± 66.15 m/s, STI: 7.96 ± 16.884, QUI: 28.8299 ± 25.461, BMDe: 0.0180 ± 0.1610 g/cm3). Multiple regression revealed that SOS, STI and QUI were statistically significant and negatively correlated with CPT Crawford classification. Conclusions We found the incidence of decreased bone strength in CPT group was higher than that in the non-bone metabolic disease group. This phenomenon was not related to NF1 but related to CPT Crawford classification, which suggested that the higher the grade of the CPT Crawford classification, the lower the bone strength and the higher the risk of fracture.